THE LEGAL PROPERTIES OF INDEMNITY AS PREVENTION OF OWNERSHIP AND IMPLEMENTATION OF CONVERSION OF LAND RIGHTS BASED ON LAW NUMBER 5 YEAR 1960 CONCERNING AGRARY BASICS - Wita Pemerhati Rasa; Subarsyah; Deden Sumantry (International Journal of Latin Notary, 2021)
Many lands have not been registered or have not had a certificate but have been owned by community members with evidence of a land certificate issued by the village head. These unregistered lands are generally found in rural areas where a village head's land certificate only proves land ownership rights. This study questions the concept of the basis for the Indemnity Certificate as the initial evidence of the implementation of the Conversion of SKGR legal status as preliminary evidence of performance and legal protection against the holder of the indemnity certificate in the implementation of the transformation based on Law No. 5 of 1960 concerning the Agrarian Principles. The research method used is descriptive analysis with normative juridical research specifications. Secondary data as primary legal material, the research stage in the form of literature study and field data and data collection techniques used in the form of literature study and to complete data are used field data, data analysis used is in the form of linking legal theory with one statutory regulation with one another. Research Results from the concept of a title in the form of a Compensation Certificate as the initial evidence of the implementation of the Conversion Based on Law No. 5 of 1960 concerning Agrarian Principles, this compensation certificate is made by interested parties, namely the party whose land is compensated and the party giving the loss (the buyer). The concept is quite simple, starting with the head of the local community's testimony, then it is found out by the Village Head that it was confirmed by the and witnesses. Legal Status of Indemnity Certificate as Preliminary Evidence of the implementation of the Conversion based on Law No. 5 of 1960 concerning Agrarian Principles, every holder of a Compensation Certificate is obliged to convert the base of their rights in the land registration system. Preventive legal protection provided to Land Ownership Certificate Holders in good faith, which is regulated in the provisions of Article 32 paragraph (1) and paragraph (2) of Government Regulation Number 24 of 1997 concerning Land Registration which states that: Paragraph (1): certificate is a proof of rights which is valid as a powerful means of burden proof.